Study of The Effect of Quercetin on some Biochemical Markers in Rabbits Exposed to Oxidative Stress (Journal of Hama University, 2021)
The research aimed to evaluate the effect of quercetin administration on the level of lipids in the blood of rabbits by studying some biochemical parameters such as Low-Density Lipoprotein (LDL), High-Density Lipoprotein (HDL) and Triglycerides (TG) in rabbits that were given hydrogen peroxide. In the experiment, (21) domestic adult rabbits were used, which were divided into three groups, the first group G1 (control) was dosed with distilled water only, while the second group G2 was dosed (10) ml of hydrogen peroxide at a concentration of 1.5% on a daily basis, while the animals in 3rd Group G3 were dosed (4) ml of quercetin at a concentration of 30 mg / kg with (10) ml of hydrogen peroxide at a concentration of 1.5% on a daily basis. LDL, HDL and TG levels were measured in all groups 30 days after the start of the experiment. The results showed significant differences at the Probability level P